Students’ Perceptions of Using the CAKE Application for Improving English Speaking Skills: A Literature Review - Yuyun Hasanati (Journal of English Education Studies, 2026)
The researcher conducted the study aiming to find out students' perceptions of using the Cake application for English speaking skills. The method used in this study was a Literature Review looking for references from journals or articles that examined the use of the Cake application for learning English, from the results of this study , most students agree with the Cake application that they are given more opportunities to improve their speaking skills, they are interested in improving their speaking skills independently through the Cake application, they are able to practice speaking using the Cake application as much as they want to be happy choosing material on the Cake application in improving speaking skills, Using the Cake application independently increases self-confidence to practice speaking skills, using the Cake application allows them to control themselves learn, using the Cake app in their own time makes learning English more interesting, the Cake app can help them solve their problems in improving speaking skills, the practice in the Cake app gives them more motivation in improving speaking skills, the Cake app is easy to use improve speaking skills . Four selected students were interviewed about the use of the Cake application to improve their speaking skills, most of them knew some of the features of the Cake application and understood how to use the application. Finally, they will recommend the app to other students to improve their speaking skills. Cake is an application that focuses on learning English. An interesting feature of this application is speaking, students can practice their speaking skills using this application